An empirical investigation of the effects of ethical climates on organizational corruption - Stachowicz-Stanusch, Agata; Simha, Aditya (Journal of Business Economics and Management, 2013)
This study investigates the effects of ethical climates on organizational corruption. Data from 200 employees from seven hospitals in Poland was used to test the specific relationships between the five empirically occurring ethical climate types (i.e. caring, instrumental, independence, law and code, and rules) and organizational corruption. Law and code climates were negatively associated with organizational corruption, while instrumental and caring climates were positively associated with organizational corruption.